miR-301a Suppression within Fibroblasts Limits the Progression of Fibrosis through the TSC1/mTOR Pathway - Jiexuan Wang; Xun Li; Mingtian Zhong; Yansheng Wang; Liming Zou; Miaomiao Wang; Xiaoli Gong; Xinjie Wang; Chengzhi Zhou; Xiaodong Ma; Ming Liu (Elsevier, 2020)
Pulmonary fibrosis has been characterized by abnormal proliferation of fibroblasts and massive deposition of the extracellular matrix, which results from a complex interplay of chronic injury and inflammatory responses. MicroRNA-301a (miR-301a) is activated by multiple inflammatory stimulators, contributing to multiple tumorigenesis and autoimmune diseases. This study showed that miR-301a was overexpressed in a bleomycin-induced murine model of pulmonary fibrosis and patients with idiopathic pulmonary fibrosis (IPF). In addition, miR-301a was activated by transforming growth factor β (TGF-β) and interleukin 6 (IL-6) in normal and IPF fibroblasts, which was markedly reversed by the signal transducer and activator of transcription 3 (STAT3) inhibitor. The genetic ablation of miR-301a in mice reduced bleomycin-induced lung fibrosis, and the downregulation of miR-301a restrained proliferation and activation of fibroblasts. Furthermore, this study demonstrated that TSC1 was a functional target of miR-301a in fibroblasts, and the negative regulation of TSC1 by miR-301a promoted the severity of pulmonary fibrosis through the mammalian target of rapamycin (mTOR) signaling pathway. The blocking of miR-301a by the intravenous injection of antagomiR-301a inhibited the proliferation of fibroblasts and the structural destruction of lung tissues in the bleomycin-induced lung fibrosis mouse model. The findings revealed the crucial role of the miR-301a/TSC1/mTOR axis in the pathogenesis of pulmonary fibrosis, suggesting that miR-301a might serve as a potential therapeutic target.